Associations of Osteoarthritis With Thrombectomy Utilization and Outcomes for Large Vessel Acute Ischemic Stroke. Issue 2 (21st December 2022) - Chen, Huanwen; Khunte, Mihir; Colasurdo, Marco; Jindal, Gaurav; Malhotra, Ajay; Gandhi, Dheeraj; Chaturvedi, Seemant
Abstract : Background: Osteoarthritis and other musculoskeletal disorders are the leading causes of disability in the United States. While osteoarthritis is not a direct risk factor for stroke, osteoarthritis may impact patient selection for endovascular thrombectomy (EVT) due to prestroke disability. This study investigates associations of osteoarthritis with EVT utilization and outcomes. Methods: This was a large-scale cross-sectional study of the 2016 to 2019 National Inpatient Sample database. Adult patients with anterior large vessel ischemic strokes were identified. Patient demographics, stroke risk factors, stroke etiology, presence of osteoarthritis, medical comorbidities, EVT, intravenous thrombolysis treatments, and discharge destinations were recorded. Primary outcome was the rate of EVT treatment. Secondary outcomes include rates of discharge to home and in-hospital mortality. Propensity score matching and multivariable logistic regression models were used to account for possible confounders. Results: Two hundred fifty-two thousand five hundred five patients were identified, of whom 8.5% (21 500 patients) had osteoarthritis. After propensity score matching for 32 clinical variables, osteoarthritis patients were found to be 17.3% less likely to receive EVT than non-osteoarthritis patients (14.4% versus 17.3%, respectively; P <0.001). In multivariable logistic regression analysis, osteoarthritis was associated with 22.6% lower odds of receiving EVT (OR, 0.77 [95% CI, 0.70–0.86]; P <0.001), an effect size larger than any medical comorbidity captured in this study other than dementia and nonstroke neurological disease. Among those treated with EVT, multivariable logistic regression models showed that osteoarthritis was not associated with different odds of being discharged home (OR, 0.99 [95% CI, 0.81–1.21]; P =0.93); however, osteoarthritis was marginally associated with lower odds of in-hospital mortality (OR, 0.74 [95% CI, 0.54–1.01]; P =0.054). Conclusions: Large vessel ischemic stroke patients with osteoarthritis were significantly less likely to receive EVT therapy despite similar post-EVT outcomes. These results warrant further investigation and prompt a critical review of current patient selection practices for stroke EVT therapy, specifically for patients with baseline disability due to musculoskeletal conditions such as osteoarthritis.